Expression and functional activity of breast cancer resistance protein (BCRP, ABCG2) transporter in the human choriocarcinoma cell line BeWo - Ceckova, Martina; Libra, Antonin; Pavek, Petr; Nachtigal, Petr; Brabec, Marianne; Fuchs, Renate; Staud, Frantisek (Clinical and experimental pharmacology & physiology, 2006)
1. Breast cancer resistance protein (BCRP, ABCG2) is a drug efflux transporter that is believed to affect the drug disposition of several drugs and xenobiotics. In the present study, we evaluated the localization and functional expression of BCRP in the human choriocarcinoma cell line BeWo, an in vitro model of the human trophoblast, and compared it with the expression of P-glycoprotein (MDR1, ABCB1) as the most widely studied placental transporter. In addition, the expression of BCRP at the mRNA level was compared with that of MDR1 in the human term placenta. 2. Western blotting analysis revealed high endogenous expression of BCRP protein in BeWo cells. Using indirect immunofluorescence microscopy, we found that the BCRP transporter appears to be localized predominantly at the apical plasma membrane. Functional studies showed a significant effect of the BCRP inhibitors GF120918 (5 micromol/L) and Ko143 (1 micromol/L) on mitoxantrone accumulation and, thus, confirmed efflux activity of BCRP in BeWo cells. 3. Using absolute mRNA quantification with real-time reverse transcription-polymerase chain reaction, we found high expression of BCRP in BeWo cells, whereas no transcript of MDR1 (P-glycoprotein), the most extensively studied drug transporter, was detected. 4. In the human placenta, BCRP was localized predominantly in the syncytiotrophoblast layer; however, immunopositivity for the BXP-21 antibody was also observed in fetal vessels of the chorionic villi. The number of BCRP transcripts in the human term placenta was found to be more than 10-fold higher compared with the expression of MDR1. 5. In conclusion, we suggest that BeWo cells could serve as a suitable in vitro model to study trans-trophoblast transport of BCRP substrates and that placental BCRP can play an important role in preventing the accumulation of potentially toxic xenobiotics in the trophoblast cells.
Keywords: buněčná membrána; Microscopy, Fluorescence; indoly; Pregnancy; regulace genové exprese u nádorů; nádorové proteiny; ATP Binding Cassette Transporter, Subfamily G, Member 2; ATP Binding Cassette Transporter, Subfamily B, Member 1; messenger RNA; Humans; Indoles; akridiny; Placenta; Female; ABC transportéry; fluorescenční mikroskopie; Tetrahydroisoquinolines; polymerázová řetězová reakce s reverzní transkripcí; Blotting, Western; Mitoxantrone; lidé; Reverse Transcriptase Polymerase Chain Reaction; zvířata; Immunohistochemistry; imunohistochemie; Choriocarcinoma; mitoxantron; Acridines; buněčné linie; RNA, Messenger; biologický transport; P-glykoprotein; ženské pohlaví; ATP-Binding Cassette Transporters; Cell Line; těhotenství; nádorové buněčné linie; tetrahydroisochinoliny; choriokarcinom; Animals; Cell Line, Tumor; Cell Membrane; Neoplasm Proteins; western blotting; placenta; Gene Expression Regulation, Neoplastic; ABC transportér z rodiny G, člen 2; Biological Transport